Concept of «Identity Transforming Organizations» (ITOs): Ideas, Criticism and Prospects for Application in Religious Studies - T. A. Folieva (Интеллект. Инновации. Инвестиции, 2021)
The article discusses the concept of “Identity Transforming Organizations” (ITOs), which was proposed by American sociologists of religion in the 70s. XX century in the course of research of the society of Alcoholics Anonymous. The purpose of such organizations is to transform the identity of the newly converted member, change his cognitive, behavioral and affective attitudes. One of the mechanisms of such transformation is encapsulation – the inclusion of a new convert into the organization, through his social, physical or ideological isolation from the outside world. Encapsulation is a social cocoon that protects an individual in a stressful situation from an external environment that becomes aggressive for him. In the course of it, the new convert acquires a new social status and role (catechuchman, Christian, alcoholic, devotee, etc.); new identity; new reference group; new life attitudes, as the affective, cognitive and behavioral components change. In addition to changing behavior, assigning a new status and forming a corresponding identity, the activities of ITO are aimed at the emergence of new reference groups and references in an individual, not only the individual himself changes, but also a change in his social environment. There are organizations in which the transformation of identity, active proselytism is one of the main internal and external processes, and there are those in which such a transformation is activated in special cases or through special units. To illustrate the concept, examples of authors associated with the organization Alcoholics Anonymous were given and texts of a Russian religious association, whose activities correlate with theoretical provisions (Preobrazhensky Brotherhood), were included. The concept presents researchers with a new toolkit in the study of socially active religious associations.